1993
DOI: 10.1007/bf00008232
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal pattern of ammonium (methylamine) uptake by phytoplankton in an oligotrophic lake

Abstract: Our primary objective was to determine if a relationship existed between seasonal change in phytoplankton and high afhnity for (K,) or uptake rates (V,,,) of ammonium which might explain seasonal phytoplankton succession in oligotrophic ecosystems. We measured ammonium uptake using ['"Clmethylamine and estimated I&, and V,,, using Hanes Plots at 2-week intervals during 6 months of thermal stratification in Mountain lake, Virginia (37" 22' N, 80" 32' W). Community composition, nutrient levels, and other variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Diatoms, MPB, and cyanophyceans are found to be dominating groups of primary producers in Chilka Lagoon during the period of study. It is well known that the diatoms and MPB utilise the available ammonia [5,26,27] in the water column for their growth during the photosynthetic activity and the amount of oxygen liberated in this process is proportional to their growth rates. Thus, the rate of oxygen liberation due to photosynthetic activity by diatoms and MPB can be given by [5] (32) (12) [ Phy Phy…”
Section: Development Of Biogeochemical Model For Do In Lake Chilkamentioning
confidence: 99%
“…Diatoms, MPB, and cyanophyceans are found to be dominating groups of primary producers in Chilka Lagoon during the period of study. It is well known that the diatoms and MPB utilise the available ammonia [5,26,27] in the water column for their growth during the photosynthetic activity and the amount of oxygen liberated in this process is proportional to their growth rates. Thus, the rate of oxygen liberation due to photosynthetic activity by diatoms and MPB can be given by [5] (32) (12) [ Phy Phy…”
Section: Development Of Biogeochemical Model For Do In Lake Chilkamentioning
confidence: 99%
“…They found that ammonium was the preferred form for uptake and seasonal variations of uptake rates correlated with changes in chlorophyll a concentration, water temperature, and day length. Parson and Parker (1993), working in Mountain Lake, Virginia, suggested that seasonal changes in the phytoplankton community in oligotrophic systems may be the result of species affinity for available ammonium. The dynamics of the Ceratium hirundella population and the abundance of dinocysts in the plankton and sediments were studied in Lake Sempach, Switzerland (Pollingher et al, 1993).…”
Section: Aquatic Biotamentioning
confidence: 99%